How inheritance law affects family firm performance: Evidence from a natural experiment - GAM, Yong Kyu (Institutional Knowledge at Singapore Management University, 2020)
We argue that changes in the inheritance system affect incentives leading to sibling rivalry among descendants and therefore have a material impact on family firm performance. Using South Korea's 1991 inheritance law reform that stipulates the equal distribution of a deceased person's property to descendants, we find that the performance and operating growth rate in family firms show significant enhancement compared with those of nonfamily firms. Moreover, the positive effects are greater for family firms that undergo a business succession with multiple sons and married daughters. Overall, our results suggest that changing to equal bequests of inheritance has a positive effect on firm value by providing better-aligned incentives to heirs in family firms. We conclude our paper by discussing the implications of our findings for current generations in family firms.